2015
DOI: 10.1016/j.genhosppsych.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Sick leave and work disability in primary care patients with recent-onset multiple medically unexplained symptoms and persistent somatoform disorders: a 10-year follow-up of the FIP study

Abstract: Both recent-onset and persistent MUS have significant long-term impact on patient functioning in regard to working life; this calls for early recognition and adequate management of MUS in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 40 publications
(49 reference statements)
6
51
1
2
Order By: Relevance
“…Moreover, participants with NFS syndromes reported higher comorbidity (47% vs. 23%) and pain disability (M difference = 4.35), which converge with earlier studies on functional impairment and comorbidity in patients with NFS syndromes (Carson, Stone, Hibberd et al, 2011;Dirkzwager & Verhaak, 2007;Fink et al, 2005;Wessely et al, 1999). Other significant demographic differences have been reported earlier as well, including that NFS syndromes were significantly associated with lower educational level (Dirkzwager & Verhaak, 2007), unemployment (Verhaak et al, 2006), and current full-time sickleave (Rask et al, 2015). While we did not measure actual frequency of healthcare visits as did Barsky et al (2005), we similarly found that participants with NFS syndromes were more likely to report that they were in regular contact with healthcare services.…”
Section: Resultssupporting
confidence: 86%
“…Moreover, participants with NFS syndromes reported higher comorbidity (47% vs. 23%) and pain disability (M difference = 4.35), which converge with earlier studies on functional impairment and comorbidity in patients with NFS syndromes (Carson, Stone, Hibberd et al, 2011;Dirkzwager & Verhaak, 2007;Fink et al, 2005;Wessely et al, 1999). Other significant demographic differences have been reported earlier as well, including that NFS syndromes were significantly associated with lower educational level (Dirkzwager & Verhaak, 2007), unemployment (Verhaak et al, 2006), and current full-time sickleave (Rask et al, 2015). While we did not measure actual frequency of healthcare visits as did Barsky et al (2005), we similarly found that participants with NFS syndromes were more likely to report that they were in regular contact with healthcare services.…”
Section: Resultssupporting
confidence: 86%
“…Associations between functional disorders and anxiety and depression are previously described [26], and an increasing number of studies suggest that persistent and multiple symptoms may lead to severe disability and poor outcome [27]. Patient-reported outcomes (PROs) are increasingly used to improve patient care as a supplement to clinical information [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Impaired quality of life and work participation in the FSS are at least as severe as those found in well-defined medical diseases with comparable symptoms [16,17]. Long-term outcome of FSS/bodily distress is variable, but for patients with multiple bodily symptoms it is poor with high rates of disability and sick leave [18]. Notably, low back and neck pain, which have at least large overlap with FSS/bodily distress, are among the top 5 in the global ranking of disability-adjusted life years [19].…”
Section: The Clinical Problem: a Matter Of Perspectivementioning
confidence: 99%